Data Analysis of Globular Cluster Harris Catalogue in View of the King Models and Their Dynamical Evolution. I. Theoretical model - Marco Merafina; Daniele Vitantoni (Acta Polytechnica CTU Proceedings)
We discuss the possibility to analyze the problem of gravothermal catastrophe in a new way, by obtaining thermodynamical equations to apply to a selfgravitating system. By using the King distribution function in the framework of statistical mechanics we treat the globular clusters evolution as a sequence of quasi-equilibrium thermodynamical states.